Genetic and neuronal mechanisms governing the sex-specific interaction between sleep and sexual behaviors in Drosophila - Dandan Chen (Nature Portfolio, 2017)
Genes and circuits involved in sleep and sexual arousal have been extensively studied in Drosophila. Here the authors identify the sex determination genes fruitless and doublesex, and a sex-specific P1-DN1 neuronal feedback that governs the interaction between these competing behaviors